Design and simulation of a solar–wind–biogas hybrid system architecture using HOMER in India. Issue 2 (3rd March 2016) - Mishra, Sambeet; Panigrahi, C.K.; Kothari, D.P.
Abstract : The renewable energy sources are accompanied by certain constraints as reliability, availability and continuous generation. In India, biomass is considered as the second best suitable combination with other renewable energy sources. Both solar and wind are undependable renewable energies as they are unpredictable. Now the key to successful renewable energy harvesting lies in the selection of hybrid system architecture for power generation. In rural areas, light is usually unavailable and if it does, it is mostly an incandescent light used for household lighting instead of fluorescent. System reliability, economy and environmental issues are the three major issues for decentralised electrification. So, finding the best suited hybrid system configuration to overcome these constraints is the need of the hour. It is at this stage that HOMER comes into the picture. HOMER, abbreviated name of hybrid optimization model for electric renewable, successfully realises system configuration before its installation and works for on-grid, off-grid and stand-alone systems, which make it useful for rural to urban applications. It simulates and optimises the best suitable solution for a hybrid system and generates reports incorporating all the aspects in designing a system. Here, a typical hybrid system is considered and the implementation of HOMER software has been incorporated.